Improving Resilience to Climate Impacts in Mali through Improved Availability, Access and Use of Climate Information: Dialogue with Users - Nenkam, Andree M.; Sibiry Traoré, Pierre C. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
The amount and quality of station climate data has been declining all over Africa. Despite a noteworthy legacy in the provision of agro-meteorological extension to farmers (Mason, 2015; Dinku, 2016) , the large landlocked country of Mali is no exception: there, a security crisis in the northern half of the country since 2012 has further aggravated the provision of data from an already sparse weather station network. This greatly hinders local decision-making processes that may benefit from the use of climate data, and affects the ability of vulnerable communities to sustain their resilience capacity in a changing environment characterized by population growth, increasing externalization of risk and expected rise in the frequency of extreme events. Restoring the availability and accessibility of quality climate data over space and time is the aim of the ENACTS (Enhancing National Climate Services) initiative, promoted by the International Research Institute for Climate and Society (IRI, at Columbia University). On November 3, 2016, ICRISAT, Mali-Meteo and IRI launched the ENACTS initiative in Mali during a national workshop to i) introduce stakeholders to Mali Meteo’s new data and web interface (Mali Meteo Data Library) and; ii) solicit feedbacks and recommendations from the national community of users. This workshop was a result of collaboration between the CCAFS-funded CASCAID project (Capacitating African Smallholder with Climate Services and Insurance Development) led by ICRISAT and ICRAF, and the USAID-funded project Building Mali Meteo’s Capacity to Deliver Improved Climate Services, led by IRI. During the workshop, participants showed high interest in the new tools and requested additional capacitation through a dedicated follow-up event targeting sectorial applications of the data library and maprooms.